MEMBANGUN LINGKUNGAN INKLUSIF DALAM STRATEGI MENDUKUNG ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR - Humaira Azka Salsabila; Cristina Natalia Enjelina; Haikal Alfa Salam; Septi Fitri Meilana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to build an inclusive environment for children with special needs, particularly students with dyslexia, in primary schools. The methodology used was a qualitative approach with a case study, which allowed for an in-depth exploration of students' experiences and challenges. Data was collected through direct observation in the classroom and interviews with a grade III teacher with experience teaching dyslexic students. The research focus included cognitive aspects, such as difficulties in reading and writing, as well as social-emotional aspects, including learning anxiety. The results showed that students with dyslexia experience significant difficulties in processing information and interacting socially, thus requiring adaptive learning strategies. Recommendations from this study include the importance of collaboration between teachers and parents, as well as the use of learning methods that involve multiple senses to create a supportive learning atmosphere. Thus, this study provides practical guidance for schools in improving the effectiveness of inclusive education for students with special needs.